Археологічні дослідження в м. Малин Житомирської обл. в 2017 р. - Ієвлєв, М.М.; Петраускас, А.В.; Тімошенко, В.І. (Археологія і давня історія України, 2019)
У роботі розглянуто результати досліджень
багатошарового городища в м. Малині. Протягом
більше ніж ста років воно привертає увагу вітчизняних археологів, які проводять на ньому розкопки, а результати польових досліджень малинського городища увійшли до підґрунтя багатьох
наукових гіпотез щодо генезису міст. Результати
останніх сезонів дозволили відкрити раніше невідомий горизонт слов'янських старожитностей та
повернутися до теми раннього формування міст у слов'янському середовищі. The first archaeological excavations at the Malyn ancient
settlement had been initiated in 1878 by V. B. Antonovych.
In the 20th century, the site has been explored
by such outstanding scientists as P. M. Tretiakov,
M. P. Kuchera, B. A. Zvizdetskyi. On the basis of the
found artifacts, the site has been attributed as one of the
earliest town settlements of the Eastern Slavs, and the
discovered materials have been used to generate the concept
of the early development of the towns in the East
Slavonic area. Starting from 2016, the expedition of the
Institute of Archaeology of the National Academy of Science
of Ukraine regularly explores the site to investigate
the fundamental issues of the early Slavonic towns in
Eastern Europe genesis. During the field season of 2017, scientists discovered the remains of the defense constructions
dating back to the earliest period of the site formation. The new data which enable to characterize the settlement
surroundings has become an important result of the research in 2017. The artifacts discovered at the surrounding
areas of the site indicate that culture layers of all the neighboring grounds available for settling (except
for the flood lands of the Irsha river) are synchronous to those found at the settlement.